Financing Durable Assets - Rampini, Adriano A. (American Economic Review, 2019)
This paper studies how the durability of assets affects financing. We show that more durable assets require larger down payments making them harder to finance, because durability affects the price of assets and hence the overall financing need more than their collateral value. Durability affects technology adoption, the choice between new and used capital, and the rent versus buy decision. Constrained firms invest in less durable assets and buy used assets. More durable assets are more likely to be rented. Economies with weak legal enforcement invest more in less durable, otherwise dominated assets and are net importers of used assets. (JEL D25, G31, G32, O31)